ANALISIS SOLVABILITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN PENERBANGAN PERIODE 2018-2023 - Rismawati; Riyana Harjayanti, Diana (Journal of Research and Publication Innovation, 2024)
This research aims to determine the financial performance of PT. AirAsia Indonesia Tbk and PT. Garuda Indonesia Tbk using solvency ratios (Debt to Asset Ratio, Debt to Equity Ratio) and profitability ratios (Return on Asset, Return on Equity, Net Profit Margin) for the period 2018-2023. The data collection technique employed is documentation and literature review, and the data analysis technique used is financial ratio analysis. The research findings indicate that the solvency ratios of PT. AirAsia Indonesia Tbk and PT. Garuda Indonesia Tbk, measured using Debt to Asset Ratio, indicate that their financial performance is in an unhealthy condition, suggesting that the assets financed by debt are more dominant than those financed by equity. Similarly, the Debt to Equity Ratio for both companies indicates an unhealthy financial condition, indicating that the capital financed by debt is more dominant than that provided by shareholders. In terms of profitability ratios, PT. AirAsia Indonesia Tbk's Return on Asset shows an unhealthy financial performance. PT. Garuda Indonesia Tbk's Return on Asset also indicates unhealthy financial performance except for the year 2022. Additionally, both companies' Return on Equity indicates unhealthy financial performance. PT. AirAsia Indonesia Tbk's Net Profit Margin shows unhealthy financial performance, while PT. Garuda Indonesia Tbk's Net Profit Margin shows unhealthy financial performance except for the year 2022.